1993
DOI: 10.1007/bf01788826
|View full text |Cite
|
Sign up to set email alerts
|

Experimental technique simulating oxalocalcic renal stone generation

Abstract: A new technique simulating some of the conditions experienced by papillar and caliceal oxalocalcic stones during the early stages of their generation was developed. This technique enables the study of how conditions prevailing at calculogenesis, such as pH, composition of urine and presence of admixtures, influence the rate of formation and development, the crystalline texture and the composition of the concretion formed. Results achieved with this technique demonstrate that: (1) an appropriate substrate alway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…These results clearly demonstrate that COM crystal formation occurred directly on the substrates with no prior formation in the liquid. As confirmed in previous papers [8] a fixed, solid surface, irrespective of its composition, in contact with urine supersaturated with certain salts in time develops stone compounds on its surface, the composition of which depends on the supersaturated salts present. Thus in these experiments where the working pH was 5 .…”
Section: Discussionsupporting
confidence: 63%
“…These results clearly demonstrate that COM crystal formation occurred directly on the substrates with no prior formation in the liquid. As confirmed in previous papers [8] a fixed, solid surface, irrespective of its composition, in contact with urine supersaturated with certain salts in time develops stone compounds on its surface, the composition of which depends on the supersaturated salts present. Thus in these experiments where the working pH was 5 .…”
Section: Discussionsupporting
confidence: 63%
“…The results shown in this paper, according to others previously presented [3][4][5][6], clearly demonstrated that when a nonprotected nonrenewed solid surface was in contact with normal synthetic urine, sooner or latter cal cium oxalate deposits develop on it through heteroge neous nucleation processes, it is also interesting to ob serve how the COM heterogeneous nucleation capacity of calcium phosphate is notably higher than the capacity of a more hydrophobic substrate such as wax. According to these results, the activity on the nucléation and growth of COM of the most polar surfaces was greater than that caused by nonpolar surfaces, thereupon being in good accordance with the finding of other authors [9].…”
Section: Discussionsupporting
confidence: 55%
“…Some authors claimed that cell endocytosis of calcium oxalate monohydrate (COM) crystals is responsible for such fixed particles formation hltp://www. karger, ch [2], Several studies show that preexistent attached parti cles of phosphates, uric acid, mucoprotein aggregates, etc., act as powerful inductors of calcium oxalate crystal formation [3][4][5][6], It must be considered that it was clearly demonstrated that calcium oxalate formation through ho mogeneous nucléation is very improbable in the condi tions prevailing in the kidney [7], Referring to the aspects about the influence of diverse substances (crystallization inhibitors) on the formation processes of such attached microuroliths, few aspects are known. In this paper the effects of citrate, phytate.…”
Section: Introductionmentioning
confidence: 99%
“…These have used artificial urine or human urine in static or continuous-flow systems [19] and usually concentrate on calcium phosphate or magnesium ammonium phosphate mineralization onto a polymer. One method, more pertinent to stone formation, has been described by Söhnel et al [20] in which CaOx was precipitated onto silicate spheres, in a manner which was claimed to be representative of papillary and calyceal stones. Calcium-and oxalate-containing salt solutions were allowed to mix and drip onto one sphere.…”
Section: Discussionmentioning
confidence: 99%